1229 Medical complexity service evaluation: a descriptive summary of care provided to children with medical complexity. (17th August 2022) - Patel, Shil; Haynes, Sarah; Hurley, Matthew
Abstract : Aims: As part of a service evaluation, the aim was to describe the care provided to the group of children and young person (CYP) who met the American Children with Medical Complexity (CMC) definition, in our hospital. Methods: Data was retrieved for all patients who were discharged between January 2018 to May 2020, at Queen's Medical Centre Nottingham, UK, a tertiary Paediatric Centre. Included were those who had a length of stay (LOS) of more than 7 days and 3 or more consultant episodes. The data was summarised descriptively. A spell was defined as 'the number of continuous days in hospital'. A consultant episode was defined as 'the number of days spent under the care of a consultant'. An admission was defined as 'physical location under a speciality's care'. Results: There were 323 patient spells for 305 patients. This accumulated in a total of 9794 bed days, with a mean LOS 30.35 days, and the longest LOS being 374 days. Twenty-four of the children and young people died during this period. The ten specialities with the longest LOS were: Paediatric Critical Care Unit (PCCU), General Paediatrics, Spinal, General Surgery, Oncology, Neurosurgery, Nephrology, Respiratory, Neurology and ENT. The mean LOS by speciality is presented in chart 1. PCCU consistently had the greatest number of episodes, summarised in table 1 . PCCU also had the most patients with repeat admissions in the same spell; with 33 children in 2018, 18 children in 2019 and 12 children in 2020. 203 children (66%) had 3 consultant episodes. However, 64 children (21%) required 5 or more consultant episodes, with 4 children (0.01%) requiring 10 or more consultant episodes and 1 child requiring 31 different consultant episodes. 293 children (91%) required admissions to 2 or 3 specialities during the study, suggesting that despite multiple consultant episodes patients often transferred between areas/specialities as well. Conclusion: Medical complexity is conceptually regarded as a combination of multiorgan system involvement from chronic health condition(s), functional limitations, ongoing use of medical technology, and high resource need/use. This CYP group are the highest risk for adverse medical, developmental, psychosocial, and family outcomes. Our key take home messages are that CMC may be a vulnerable group due to their requirement of a prolonged LOS. In particular are the CYP group who were admitted to PCCU multiple times, require multiple consultant/speciality care with a significant proportion dying in that admission, or soon afterwards. Co-ordination of care for them and their families is therefore important, and something which we are looking to improve in our hospital.